2013
DOI: 10.3109/09513590.2013.801437
|View full text |Cite
|
Sign up to set email alerts
|

VEGF, PIGF and HIF-1α in placentas of early- and late-onset pre-eclamptic patients

Abstract: The results of the study indicated that there is no relationship between the time of onset of pre-eclampsia and the placental changes that occur in these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…HIF-1a and HIF-2a protein levels were found significantly higher in preeclamptic placentas [14,15]. In our previous study, we had observed higher levels of HIF-1a in both early and late onset preeclamptic placentas than normal controls, similar to findings of other previous published studies [16]. However, in this study, we found lower HIF-1a levels in maternal blood samples of preeclampsia group and no difference in umbilical cord blood samples when compared to controls.…”
Section: Discussionsupporting
confidence: 78%
“…HIF-1a and HIF-2a protein levels were found significantly higher in preeclamptic placentas [14,15]. In our previous study, we had observed higher levels of HIF-1a in both early and late onset preeclamptic placentas than normal controls, similar to findings of other previous published studies [16]. However, in this study, we found lower HIF-1a levels in maternal blood samples of preeclampsia group and no difference in umbilical cord blood samples when compared to controls.…”
Section: Discussionsupporting
confidence: 78%
“…Levels of HIF-1a in the placentas of preeclamptic patients have been found to be higher than the levels in placentas of healthy pregnant women (Tal, 2012;Sezer et al, 2013).…”
Section: Flt1mentioning
confidence: 83%
“…Nevertheless, placenta hypoxia can be present in LOPE as suggested for increased placental expression of hypoxia inducible factor [31]. Then, even increased angiogenesis observed in LOPE may be insufficient to overcome both the reduced oxygen delivery that is due to the infarcted placenta and the reduced oxygen delivery that would be predicted with failed remodeling of the maternal spiral arteries supplying the intervillous space [32].…”
Section: Discussionmentioning
confidence: 99%